Pengaruh Brand Image dan Content Marketing terhadap Loyalitas Konsumen melalui Brand Engagement Pada Platform Tiktok Shop - Darmawan, Roslinda Jasmine; Dara, Satria Danur; Basori, Mohamat; Akbarona, Danang Aziz (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the influence of brand image and content marketing on consumer loyalty, both directly and indirectly through brand engagement on the TikTok Shop platform. The method used is a quantitative approach with data collection through questionnaires from 211 TikTok Shop user respondents. Data processing was carried out using SmartPLS 3.0 software with Structural Equation Modeling (SEM) techniques. The results of the study indicate that brand image and content marketing have a significant effect on brand engagement. Meanwhile, brand engagement has a significant effect on consumer loyalty and mediates the relationship between brand image and content marketing on consumer loyalty. These findings emphasize the importance of emotional engagement and active consumer interaction with brands through creative content and positive images in forming long-term loyalty. This study provides theoretical contributions to the development of digital marketing as well as practical recommendations for business actors in utilizing TikTok Shop as a strategic marketing platform.